Determinants of credit risk in the banking system in Sub-Saharan Africa - Trust R. Mpofu; Eftychia Nikolaidou (Review of Development Finance, 2018)
This paper investigates the macroeconomic determinants of credit risk in the banking system of 22 Sub-Saharan African economies. We measure credit risk as the ratio of non-performing loans to total gross loans (NPLs) and employ dynamic panel data methods over the period 2000-2016. Using a variety of specifications, the results show that an increase in real GDP growth rate has a statistically and economically significant reducing effect on the ratio of non-performing loans to total gross loans. Furthermore, inflation rate, domestic credit to private sector by banks as a percent of GDP, trade openness, VIX as a proxy of global volatility, and the 2008/2009 global financial crisis, all have positive and significant impact on NPLs.
Keywords: E44; G21; 650; Non-performing loans; Macroeconomic factors; Banking system; Panel data; Sub-Saharan Africa